FEASIBILITY STUDY OF HYBRID THERMOELECTRIC PLANTS USING CSP TECHNOLOGY AND FOSSIL FUEL: SIMULATION SCENARIOS - Lisboa, Fabio C. de; Rodrigues, A. C.; Cavalcante, A.M. G.; Siqueira, M. B.; Guiné, J. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Due to the rapid advance in technology, a new generation of power plants has emerged: the concentrated solar power (CSP). It is a renewable energy system that can be combined with large-scale energy storage systems. CSP holds many promises for the countries with high direct solar radiation, as Brazil. However, there are many problems regarding the viability of these plants in the emerging countries such as high capital costs, lack of national technology and qualified professionals. Hybridization of existing power plants with solar energy could be a possible gateway for the technology deployment. This paper presents the technical and economic feasibility analysis of a steam super-heater plant powered by CSP for electricity production. Such hybridization permits the reduction of CO2 emissions and retrenchment in the long term. In this context, the performances of four different systems of thermoelectric power generation were compared: (i) solar reheating - superheated steam generated by boiler and it expansion in the first turbine using CSP for reheating second expansion turbine; (ii) solar superheater - generating saturated steam in a boiler and superheating it using CSP; (iii) supercritical solar heater - saturated steam production in a boiler and heating at supercritical steam in CSP and (iv) conventional cycle and CSP working in parallel. The direct irradiation data available at the Brazilian solar atlas were analyzed, looking for the best location of power plant installation. In addition to the solar resource data, other criteria as economic, environmental and availability of transmission lines were taken into account. The decision matrix with performance indicators helped in the decision-making process of location selection. Comparing to others scenarios the obtained results showed several advantages of scenario (iv) - conventional cycle and CSP working in parallel using solar power towers without thermal storage. Research result as well revealed Santa Maria da Vitória town, Bahia region, as a better place for plant construction using the selected scenario. The total capacity was determined to be 30 MWe in accordance with the incentives offered by 481/2012-ANEEL (Brazilian Agency) resolution. Keywords: Concentrated solar power (CSP); Solar irradiation data; Hybrid thermoelectric; Reheating vapor cycle.